2021
DOI: 10.4103/jcd.jcd_57_21
|View full text |Cite
|
Sign up to set email alerts
|

Application of cone-beam computed tomography in the management of dilacerated maxillary central incisor associated with radicular cyst and external root resorption - A case report

Abstract: The maxillary anterior region is the most common site for the occurrence of radicular cyst in permanent dentition, because of a high frequency of trauma in this region. As radicular cyst is categorized as an inflammatory cyst, endodontic treatment of the tooth associated with the cyst becomes a part of the treatment regimen. Management of radicular cyst becomes challenging when it involves tooth with complex root morphology. This report presents the diagnosis and successful management of a dilacerated maxillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…[ 2 3 4 ] History of trauma may be elucidated in many other cases, particularly in children and young adults. [ 5 6 ] However, in some cases, with large carious lesions in children with good host immune response, instead of necrosis, the pulp shows hyperplasia which is regarded as pulp polyp/chronic hyperplastic pulpitis. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 3 4 ] History of trauma may be elucidated in many other cases, particularly in children and young adults. [ 5 6 ] However, in some cases, with large carious lesions in children with good host immune response, instead of necrosis, the pulp shows hyperplasia which is regarded as pulp polyp/chronic hyperplastic pulpitis. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…1 The use of a CBCT scan can greatly assist clinicians to visualise the tooth in three dimensions, enable the assessment of crown and root morphology, canal configuration, the degree of root resorption of the adjacent teeth, and the presence of a periapical lesion. 19 The clinical management of an impacted dilacerated tooth is usually challenging, time consuming, costly, and often requires multidisciplinary triaging to deliver treatment. It has been found that 35% of impacted maxillary incisors have been associated with dilaceration.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%